Rhodotorula mucilaginosa as a cause of persistent femoral nonunion - Goyal R (Journal of Postgraduate Medicine, 2008)
We present a case of postoperative infection which presented as nonunion fracture femur in a 30-year-old man due to Rhodotorula mucilaginosa . This is the first report of Rhodotorula infection in a patient with fracture nonunion. The patient underwent repeated surgical debridement and received intensive antibiotic therapy before the diagnosis was made. The diagnosis could have been made earlier if the fungal etiology had been suspected earlier. Early suspicion and diagnosis of infection with atypical yeasts could be under-reported because of difficulties in accurate diagnosis and a tendency of attributing isolates to specimen contamination.